The learning and transfer of motor skills in the group teaching of functional piano skills (Orfeu, 2018)
This paper aims to present research in progress in the field of piano teaching, pointing out the factors that favor the learning and transfer of motor skills, especially in the context of collective teaching, with the objective of enhancing piano learning as a complementary instrument in higher education. The methodology used is actionresearch; it was carried out over two semesters of the Functional Piano  iscipline at the Federal University of Paraná (UFPR, Brazil). Currently undergoing data analysis, the research seeks to raise and discuss issues related to motor learning and the possible use of teaching strategies aimed at learning and transferring motor skills to the piano. In this article, the concepts of motor skill and transfer of motor learning are discussed, as well as some aspects of the practice that can favor motor learning and transference: goal setting, attention focus, pre-practice reference, random practice and block practice, and collaborative learning. Finally, the current situation of the research and its ongoing development is presented.
Keywords: Motor learning; Functional skills; Group piano; Piano teaching